Accuracy of transcranial brain parenchyma sonography in the diagnosis of dementia with Lewy bodies. (1st May 2016) - Favaretto, S.; Walter, U.; Baracchini, C.; Pompanin, S.; Bussè, C.; Zorzi, G.; Ermani, M.; Cagnin, A.
Abstract : Background and purpose: Transcranial sonography (TCS) of the brain parenchyma is used to visualize alterations in the substantia nigra (SN) and it is applied for early diagnosis of Parkinson's disease. Our aim was to explore specific echogenic alterations of the SN in dementia with Lewy bodies (DLB) compared to Alzheimer's disease (AD). Methods: Seventy‐one subjects underwent TCS: 22 DLB, 28 AD and 21 healthy elderly controls. Cognitive impairment, extrapyramidal signs, visual hallucinations, fluctuations and rapid eye movement sleep behaviour symptoms were investigated. TCS assessed SN hyperechogenicity and symmetry. Results: Transcranial sonography revealed SN hyperechogenicity in 100% of DLB compared to 50% of AD and 30% of controls. Mean SN echogenic area (cm 2 ) was 0.22 ± 0.03 in DLB, 0.15 ± 0.03 in AD and 0.14 ± 0.03 in controls ( P < 0.0001). More than 50% of DLB presented a marked hyperechogenicity (cutoff value >0.22 cm 2 ) compared to only 10% of AD ( P < 0.0003). DLB had symmetrical SN enlargement, whereas AD were mostly asymmetrical ( P = 0.015). A combination of SN echogenic area and asymmetry index had a sensitivity of 88.9% and a specificity of 81.2% in discriminating DLB from AD (positive predictive value 85.7%, negative predictive value 85.7%). No association was found between SN hyperechogenicity and Unified Parkinson's Disease Rating Scale part III, Mini Mental State Examination or the presence of visual hallucinations. Conclusions: Transcranial sonography may be a valid supportive tool in the diagnostic workup of neurodegenerative dementia helping clinicians to distinguish DLB from AD even at the early stages.